Multi-Component Comparative Pharmacokinetics in Rats After Oral Administration of Fructus aurantii Extract, Naringin, Neohesperidin, and Naringin-Neohesperidin - Yuan, Jinbin; Wei, Feiting; Luo, Xizhen; Zhang, Min; Qiao, Rifa; Zhong, Minyong; Chen, Haifang; Yang, Wuliang (Frontiers in Pharmacology, 2020)
Fructus Aurantii (FA) has been largely used as Qi-invigorating herb in China for centuries. The main components (meranzin hydrate, naringin, neohesperidin, meranzin, nobiletin) have good physiological activity with relatively high abundance in FA. Few multi-component comparative pharmacokinetics are simultaneously accessible for the flavone glycosides, polymethoxy flavones and coumarins in FA. In this work, a reliable and rapid ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method was established and validated to determine the five ingredients in the SD rat plasma, and further applied to the pharmacokinetic studies after oral administration of monomer, drugs in compatibility and FA extract. After hydrolysis with β-glucuronidase and sulfatase, the concentration of naringin and neohesperidin in rat plasma were expressed respectively by the total concentration of naringenin and hesperitin which was determined by UPLC-MS/MS. Double-peak phenomenon was observed for naringin and neohesperidin, which may be due to the enterohepatic circulation or multiple site absorption of the two flavone glycosides. Meranzin hydrate and meranzin (coumarins) were absorbed rapidly (Tmax, about 1.0 h) but eliminated slowly (t1/2z exceeds 6.5 h). Nobiletin, a typical polymethoxy flavone, was also rapidly absorbed according to Tmax and AUC(0-t). DAS 3.1 software suggests the pharmacokinetic profiles of the five components in rats be depicted as a two-compartment pharmacokinetic model. There were significant differences in pharmacokinetic parameters for naringenin and hesperetin between the compatibility, FA extract group vs monomer group: ① remarkable increases in the values of AUC(0–∞), AUC(0–t) and Cmax; ② obvious decrease of CLZ/F; and ③ longer tmax and t1/2z. The results suggest that compatibility can promote mutual absorption and affect the elimination behaviors.